Outcomes of extremely premature infants with twin–twin transfusion syndrome treated by laser therapy. (November 2018) - Sommer, Julie; Nuyt, Anne-Monique; Audibert, François; Dorval, Véronique; Wavrant, Sandrine; Altit, Gabriel; Lapointe, Anie
Abstract Objective To compare short-term and long-term outcomes of preterm infants born at <29 weeks of gestational age (GA) with twin–twin transfusion syndrome (TTTS) treated with laser therapy to preterm twin infants without TTTS. Design Retrospective case–control study comparing 33 preterm TTTS twins to 101 preterm diamniotic–dichorionic (di–di) twins born at our institution between 2006 and 2015. Results GA at birth were 26.4 ± 1.4 weeks (TTTS) and 26.9 ± 1.6 weeks (di–di) (p = 0.07). TTTS premature newborns were less exposed to antenatal steroids (p = 0.01), more frequently born by C-section (p = 0.005), received more surfactant therapy (p = 0.004, and were smaller for GA (p < 0.001). When adjusted for antenatal steroids and birth weight, TTTS status was not associated with increased mortality (HR 1.66, 95% CI 0.77–3.56, p = 0.20). No differences were found on neurodevelopmental outcomes at 18 months of corrected GA. Conclusion Premature TTTS newborns treated with fetal laser therapy had similar survival and neurodevelopmental outcomes compared to preterm di–di twins without TTTS.